Relationship between Stress Level and Risk of Eating Disorder in Undergraduate Students during the COVID-19 Pandemic - Clara, Jessica; Hadiati, Titis; Jusup, Innawati; Sarjana A.S., Widodo (Medica Hospitalia : Journal of Clinical Medicine, 2023)
BACKGROUND: The prevalence of undergraduate students' stress before COVID-19 pandemic in Indonesia was 36.7-71.6%, where undergraduate students' age was classified as the age group for the onset of eating disorders. During the COVID-19 pandemic, students must continue their studies. However, modifications of daily routines in pandemic have a negative effect on mental health, increase negative stress (distress), and it could increase the incidence of eating disorders symptoms. AIMS:  The purpose of this study was to find out the relationship between stress level in undergraduate student and the risk of eating disorder they might have during the COVID-19 Pandemic. METHOD: This study used cross sectional study design and conducted on June 2021. The subjects were 110 active students who studied in Faculty of Medicine Diponegoro University who was chosen using consecutive sampling technique. The Perceived Stress Scale-10 questionnaire was used to measure the students’ stress level for the past month and the Eating Attitude Test-26 questionnaire was used to determine the students' risk of having an eating disoder. Both questionnaires were selected because it has been proven as reliable questionnaires with high sensitivity and specificity (Cronbach's alpha >0.7). RESULT:  The result showed that out of 110 students who have been subjects of this study, 25,5% of respondents experienced low stress, 68,2% of respondents experienced moderate stress, and 6,4% of respondents experienced high stress. It also showed that 4,5% of respondents have the risk of having an eating disorder. CONCLUSION: There is a significant correlation (p=0,005) between the stress level and risk of eating disorder with very weak positive relationship direction (r=0,097).